Tinjauan Yuridis Terhadap Tindakan Merusak Barang Orang Lain Tanpa Sengaja - Latri, Akhdan Adityo; Ramadhan, Niko Rafael; Dorinda S, Gabriel; Ginting, Yovani Yolanda Putri; Kusuma, Nanda Putri Andana; W, Yuliana Yuli (Media Hukum Indonesia (MHI), 2024)
This research discusses the juridical review of the act of accidentally damaging other people's property in the legal context in Indonesia. The main focus of this study is on the provisions of civil and criminal law that regulate responsibility and legal consequences of such actions. In civil law, the act of accidentally damaging property is regulated by Article 1365 of the Civil Code (KUHPerdata) which states that every unlawful act that causes loss is obliged to compensate for the loss, including actions caused by negligence. On the other hand, criminal law, through Article 406 paragraph (1) of the Criminal Code (KUHP), requires an element of intent to be subject to criminal sanctions. This research found that the act of accidentally damaging other people's property generally does not meet the criminal elements because there is no malicious intent, so it is more often resolved in the civil realm with a claim for compensation. Peaceful dispute resolution through mediation or negotiation was also identified as a method frequently used in practice to resolve these types of cases. This research provides a deeper understanding of how the Indonesian legal system handles cases of accidental damage to goods, as well as the legal implications for the parties involved.